Maternal Age, Nutrition and Literacy; Targeting the Root Cause for Undernutrition in Children under the Age of Two Years. - Attia Bari; Nabila Mushtaq; Rashidah Jawed; Habib Ullah; Ahsan Waheed Rathore (University of Lahore, 2022)
Objective: To analyze the risk factors for child undernutrition in mothers of malnourished children under the age of 2 years. Methods: This cross-sectional study was conducted at the Pediatric Medicine Department of The Children's Hospital Lahore from January to December, 2019. A total of 210 malnourished children in the age bracket of 2 months to 24 months and accompanying mothers admitted in the Stabilization Center for nutritional rehabilitation were included. Demographic characteristics of children and their mothers were taken. Results: Out of a total of 210 children there was slight male preponderance 116 (55%). Mean age of children was 8.89 + 6.74 months.  During first six months of life, only 31 (15%) were exclusively breast fed and in six months or older children weaning food was not started at appropriate age in 91 (43%). Illiteracy was more in mothers as compared to fathers 140 (66.7%) vs 82 (39%). Half 104 (49.5%) of the mothers had satisfactory BMI of 18.5-23 kg/m2 and remaining were either severely under nourished or overweight/obese. With advancing age significantly more mothers were obese 17% as compared to 2.4% in younger age (18-25 years) (p= 0.007).  Improper weaning practice was significantly more in mother of younger age group (p=0.023). A significant number of children who were older than six months of age and in whom weaning was not started at appropriate age had WHZ score <-3SD (p=0.019). There was no association of maternal nutrition, maternal/paternal education with the nutritional status of children (p=>0.05). Conclusion: Maternal illiteracy and both undernutrition and overweight/obesity were prevalent among the mother of undernourished children under the age of two years. Improper weaning was the major contributing factor in child's malnutrition and improper weaning practice was significantly more in mother of younger age group.